Self‐assembly of polymers from multicomponent reactions. Issue 5 (8th January 2022) - Liu, Hongxu; Kanjilal, Pintu; Thayumanavan, S
Abstract: Supramolecular assemblies from synthetic polymers have been widely used in materials science and biological applications. Developing convenient and efficient methods to tune polymer structures and architectures is important for achieving desired self‐assembly behaviors. Among various synthetic strategies, multicomponent reactions have drawn significant interest due to the high reaction efficiency, chemical selectivity, atom economy and one‐pot manner. These features make it convenient to manipulate polymer properties by varying chemical building blocks. In this review, we summarize the recent advances in the self‐assembly of polymers from multicomponent reactions. We discuss how multicomponent reactions are applied for polymerization and post‐polymerization modifications, generating polymers with specific self‐assembly behaviors for various research and application purposes. Challenges and perspectives about the development of this field are also discussed. © 2021 Society of Industrial Chemistry. Abstract : This review discusses how multicomponent reactions are applied for polymerization and post‐polymerization modifications, generating polymers with specific self‐assembly behaviors for various research and application purposes.